Assessing the Impact of Accounting Standards and Human Capital on Public Financial Reporting Quality in Indonesia - Hutahaean, Marlia Olivia; Manurung, Amran; Saribu, Ardin Dolok (Golden Ratio of Data in Summary, 2025)
The quality of village financial reporting in Indonesia remains a concern, with inconsistencies and inadequacies still evident in many regions, including Bintang Bayu Sub-district. This study examines the effect of Government Accounting Standards (SAP) implementation and human resource (HR) competency on the quality of village financial reports. Employing a quantitative approach, primary data were collected through a structured Likert-scale questionnaire distributed to village officials across 19 villages in the region. Data analysis was conducted using SPSS version 25. The findings reveal that both the implementation of SAP and HR competency positively and significantly affect the quality of financial reporting. Specifically, SAP implementation shows a t-value of 2.959 (p = 0.005), while HR competency records a t-value of 2.398 (p = 0.022), indicating strong statistical support. These results underscore the importance of consistent accounting standards and the competency of village personnel in enhancing financial reporting quality. This study offers practical implications for local governments, recommending targeted technical training and capacity building initiatives for village apparatus. Future research is encouraged to incorporate additional variables, such as internal audit functions and adopting accounting information systems.